Initial Experiences in Adolescents and Young Adults with T-Cell Acute Lymphoblastic Leukemia/Lymphoma Treated with the Modified BFM 2002 Protocol in a Resource-Constrained Setting - Jinwala, Prutha; Patidar, Rajesh; Bansal, Shashank; Asati, Vikas; Shrivastava, S.P.; Elhence, Aditya; Patel, Swati; Chitalkar, P.G. (South Asian Journal of Cancer, 2023)
T-cell acute lymphoblastic leukemia/lymphoblastic lymphoma (T-ALL/LBL) in adolescents and young adults (AYAs) is a clinically aggressive malignancy and life-threatening at diagnosis. Intensive chemotherapy protocols, inspired by the Berlin-Frankfurt-Münster (BFM) regimen, along with central nervous system (CNS) prophylaxis, have achieved a 75 to 85% 5-year disease-free survival rate. However, in cases of marrow and CNS relapses, second-line chemotherapy is usually ineffective. This study aimed to assess the safety and efficacy of the BFM 2002 protocol and to correlate clinical profiles and prognostic factors with survival outcomes in AYA T-ALL/LBL patients. We retrospectively analyzed data from T-ALL/LBL patients treated at the Department of Medical Oncology, Sri Aurobindo Institute of Medical Sciences (SAIMS), Indore, between 2018 and 2021. Twenty-one patients aged 15 to 29 years were studied for their clinical course and laboratory parameters over 36 months. Diagnosis and risk stratification were performed following the guidelines of the BFM 2002 protocol. All patients received treatment and monitoring according to this pediatric-inspired protocol. The median age of the patients was 17 years (range: 15–28 years). Eleven patients presented with mediastinal lymph node enlargement, 10% exhibited CNS involvement, and none had testicular involvement. Eleven patients had marrow blasts greater than 25%, indicative of acute lymphoblastic leukemia. All 21 patients were treated according to the intensive modified BFM 2002 protocol and achieved morphological remission after a median follow-up of 24 months (range: 18–36 months). Seventeen patients achieved minimal residual disease (MRD) negativity post-induction. MRD at day 33 showed a significant association with the probability of disease relapse (p = 0.0015). There were five deaths (24%), one due to toxicity and four due to relapse. The study recorded an 18-month overall survival of 76%. These results were achieved despite financial constraints. Data were entered into a spreadsheet, and statistical analysis was performed using IBM SPSS version 23. Continuous data are presented as ranges and medians, while categorical variables are shown as percentages and numbers. A chi-squared test for association, with a significance level set at p < 0.05, was conducted as indicated. AYA T-ALL/LBL requires intensive treatment regimens. With biological characterization of LBL/ALL and close therapy monitoring, encouraging outcomes can be achieved even in resource-limited settings.
Keywords: Aya; BFM 2002; interim response; MRD; T-ALL; T-LBL